2021
DOI: 10.1073/pnas.2016962118
|View full text |Cite
|
Sign up to set email alerts
|

Selective promiscuity in the binding of E. coli Hsp70 to an unfolded protein

Abstract: Heat shock protein 70 (Hsp70) chaperones bind many different sequences and discriminate between incompletely folded and folded clients. Most research into the origins of this “selective promiscuity” has relied on short peptides as substrates to dissect the binding, but much less is known about how Hsp70s bind full-length client proteins. Here, we connect detailed structural analyses of complexes between the Escherichia coli Hsp70 (DnaK) substrate-binding domain (SBD) and peptides encompassing five potential bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…Indeed, the yeast PQC E3 San1 appears to broadly recognize exposed hydrophobicity rather than specific sequence motifs 25, 44 . Other PQC E3s such as Ubr1 45 and STUB1/CHIP 46 have relegated substrate recognition to molecular chaperones, who also display promiscuity in their substrate selection 47, 48 . Second, there is likely extensive redundancy in the components of the PQC system including E3 enzymes, chaperones and adaptor proteins 16, 26, 4951 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the yeast PQC E3 San1 appears to broadly recognize exposed hydrophobicity rather than specific sequence motifs 25, 44 . Other PQC E3s such as Ubr1 45 and STUB1/CHIP 46 have relegated substrate recognition to molecular chaperones, who also display promiscuity in their substrate selection 47, 48 . Second, there is likely extensive redundancy in the components of the PQC system including E3 enzymes, chaperones and adaptor proteins 16, 26, 4951 .…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have aimed at clarifying the sequence features that constitute good Hsp70-binding elements (Clerico et al, 2021; Durme et al, 2009; McCarty et al, 1995; Nordquist et al, 2021; Rüdiger et al, 1997; Zhu et al, 1996). Degron sequences appear to hold similar features, and unsurprisingly, we find that residues flanking the degron motif also critically affect the degron activity.…”
Section: Discussionmentioning
confidence: 99%
“…DnaK, a member of the Hsp70 family in E. coli , recognizes ~700 client proteins, including multidomain proteins [ 57 ]. Although several important biochemical and structural studies have been reported for Hsp70/DnaK [ 52 , 53 , 58 , 59 ], an important NMR study, using DNA-binding domain of human telomere repeat-binding factor 1 (hTRF1) as client protein, has reported that hTRF1 exists in equilibrium between unfolded and folded states in solution [ 60 ]. NMR data showed that the conformational landscape of hTRF1 increased upon interaction with DnaK.…”
Section: Structural Studies Of Chaperone–client Complexesmentioning
confidence: 99%